2003
DOI: 10.1016/s0012-1606(03)00394-4
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Sonic Hedgehog suppresses embryonic hair follicle morphogenesis

Abstract: The Sonic Hedgehog (Shh) signalling pathway plays a central role in the development of the skin and hair follicle and is a major determinant of skin tumorigenesis, most notably of basal cell carcinoma (BCC). Various mouse models involving either ablation or overexpression of key members of the Shh signalling pathway display a range of skin tumours. To further examine the role of Shh in skin development, we have overexpressed Shh in a subset of interfollicular basal cells from 12.5 dpc under the control of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 50 publications
2
37
0
1
Order By: Relevance
“…It has to be stressed that the proteins originating from the complex structure of skin layers and regulating its keratinization may behave differently in various contexts [60,61]. When we compared our data with the analysis of Hudson et al, who suggested that coordinated over-expression of EDC genes is a hallmark of skin squamous cell carcinoma, we reached similar global conclusions [15].…”
Section: Discussionsupporting
confidence: 73%
“…It has to be stressed that the proteins originating from the complex structure of skin layers and regulating its keratinization may behave differently in various contexts [60,61]. When we compared our data with the analysis of Hudson et al, who suggested that coordinated over-expression of EDC genes is a hallmark of skin squamous cell carcinoma, we reached similar global conclusions [15].…”
Section: Discussionsupporting
confidence: 73%
“…However, we have recently shown that overexpression of hedgehog in only a subset of basal cells, using the human K1 promoter (hK1), results in the ablation of embryonic hair follicle development and does not give rise to BCC (Ellis et al, 2003). The overexpression of hedgehog via the hK1 promoter drives hedgehog activity in committed epidermal cells, thus only in a small subset (20-30%) of basal cells, the PMDpopulation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, increased or reduced expression levels for certain genes, including Hoxc13 (Godwin and Capecchi, 1998;Tkatchenko et al, 2001), BMP genes (Blessing et al, 1996;Botchkarev et al, 2002) and Notch1 (Uyttendaele et al, 2004;Vauclair et al, 2005), associated with the signaling mechanisms in hair formation appear to exert similar effects. However, for the majority of genes, it becomes increasingly apparent that their exact temporal and spatial expression is crucial; whereas reduction in Shh expression levels results in disturbed HF growth (St-Jacques et al, 1998), its increase leads to epidermal hyper-proliferation with distinct phenotypic features (Ellis et al, 2003).…”
Section: Gata3mentioning
confidence: 99%